AMINO-GRAFTED MESOPOROUS SILICA NANOPARTICLES: ASSESSMENT OF NEUROMODULATORY, MEMBRANOTROPIC AND ANTIOXIDANT PROPERTIES IN CORTEX NERVE TERMINALS - S. O. Sotnik; I. M. Pavliei; O.O. Pariiska; Y.I. Kurys; M.V. Dudarenko; A.А. Borysov; N. V. Krisanova; N. G. Pozdnyakova; L. M. Kalynovska; M. M. Driuk; A. O. Pastukhov; A. S. Tarasenko; et al. (Biotechnologia Acta)
Aim. In biomedical applications, silica nanoparticles are promising for controlled drug delivery. Also, from an environmental point of view, silica accounts for the most significant part of the mass of air pollution, particularly matter components, especially during sand dust storms.